(untitled) (Journal of the College of Basic Education, 2022)
Palm trees are considered one of the most important types of fruit because of their nutritional value and economic benefit". "They outweigh all other types of fruit trees. Therefore, the heavenly books and the prophetic Sunnah" took care of the palm tree in many habitats, and can open broad horizons by developing and cultivating more palm trees to benefit from them, especially Desert societies, and that importance was not limited to nutritional and economic value only", but added to its importance in the field of animal feed industry", and through a field survey of some palm" tree groves in the governorates (Diyala, Baghdad, Babil, Karbala", Qadisiyah", Basra) show that a single palm An average of (25) kg of waste is dumped annually", This indicates the tremendous amount of accumulation of waste that is not utilized from it", which constitutes a serious environmental problem", which necessitated the need to find alternatives for the establishment of transformative industrial projects similar to those in some Arab countries that were able through accurate scientific research for a number of researchers in the use of palm tree waste". From palm leaves", agony, fiber and trunk as alternative raw materials in the animal feed industry, which prompted the researcher to prepare a similar study based on the experiment in using" palm fronds from orchards spread around the city of Baghdad when pruning trees as a source of fodder after conducting a series of operations on it in terms of drying", cutting and spraying With urea solution" , For the purpose of experimenting with the appropriate forage produced, three rams of similar type Awassi were used in their lifetime (one year) and their weights (44-46)" kg in three experiments" other than digestion for the purpose of estimating the factors of digestion of food compounds in potato stems and treated palm and untreated urea when presented with crushed Barley grains for the period from 1/9/2018 to 11/30/2018". After calculating the digestibility factors for experimental fodder, the results showed that the rates of digestion of dry matter, protein, fat, raw fibers", dissolved carbohydrates and organic matter were significantly higher at the probability level (5%)" in stalks. Potatoes than they were in treated and untreated palm fronds where they were (62,8%, 67,5%, 77,3%, 57,8%, 64,7%, 64,8%)"" The results also showed that the food compounds transactions were significantly and significantly at the level of probability (5%) for the rams that dealt with adoption of palm fronds treated with urea at values amounting to (45,8%, 16,4%, 46,7%, 54,7% 50,3%, 47,7%)"" compared to those that dealt with untreated fronds with values that amounted to( 28,3%, 3,4%, 57,3%, 40,5%, 39,5%, 33, 6%)" From this it follows the effect of the effectiveness of the use of palm fronds (the subject of the research)" as a source of coarse feed after treatment with urea in ruminant diets mixed with barley grains without having any negative effect on them"".